Mempertahankan Varietas Padi Lokal sebagai Pilihan Strategis dalam Menjaga Efisiensi dan Ketahanan Ekonomi: Studi pada Petani Padi di Desa Sungai Rambah, Kecamatan Sambas - Novita, Uray Dian (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to identify and analyze the factors underlying farmers’ decisions to preserve local rice seeds, particularly the Sampit and Kakbulat varieties, in Sungai Rambah Village. The research employed a qualitative descriptive method, with data collected through observation, interviews, documentation, and questionnaires involving 23 farmers selected using a convenience sampling technique. The data were analyzed tabulatively in percentage form and further reinforced using a Likert scale approach. The findings indicate that farmers in Sungai Rambah Village preserve local seeds due to knowledge (100%), experience (100%), habitual practices (91%), and capital efficiency (100% relying on self-funding without significant costs). Moreover, biological (95.65%), psychological (97.83%), and environmental (91.30%) factors also influence their decision to maintain local seeds. In-depth interviews further revealed that local seeds are considered more efficient, resilient to extreme weather conditions, and are deeply embedded in the farmers’ inherited cultural practices.